The Influence Of The Basic Dimensions Of Integrated Marketing Communication On Customer Loyalty At Luxury Hotels (Study At Intercontinental Hotel Bandung Dago Pakar) - Dendy Shobron Rizaldy; Susanne Dida; Subekti Wirabhuana Priyadharma (UNIVERSITAS PAKUAN, 2024)
Above Due to intense competition in the business sector, businesses that use marketing concepts prioritise consumer pleasure, which includes developments in the high-end lodging and hospitality industries. The demands and preferences of customers must serve as the foundation for the marketing strategy that is developed as a plan to accomplish these objectives. Ultimately, positive relationships will be established between businesses and customers. Quantitative research methodologies are used in this study. 90 respondents who are categorised as loyal customers—those who have visited the same property at least twice—were given questionnaires in order to assess the relationship between IMC implementation and customer loyalty using a new measuring scale. Due to intense competition in the business sector, businesses that use marketing concepts prioritise consumer pleasure, which includes developments in the high-end lodging and hospitality industries. The demands and preferences of customers must serve as the foundation for the marketing strategy that is developed as a plan to accomplish these objectives. Ultimately, positive relationships will be established between businesses and customers. Quantitative research methodologies are used in this study. 90 respondents who are categorised as loyal customers—those who have stayed more than twice during that time—were given questionnaires in order to assess the relationship between IMC implementation and customer loyalty using a separate measuring scale. At 83.4%, integrated marketing communication has a significant impact on InterContinental Bandung Dago Pakar customers’ loyalty. However, additional variables not included in this study have an impact on the remaining 16.6%.